Unhomed at home : a postcolonial reading of Sherman Alexie’s “The Search Engine” - Usa Padgate, (Penerbit Universiti Kebangsaan Malaysia, 2021)
“The Search Engine” is a short story by Native American writer Sherman Alexie. The story depicts a quest undertaken by a young urban Indigenous woman to find an enigmatic Indian poet and, by extension, her own postcolonial self. This article proposes to read Alexie’s “The Search Engine” through the lens of postcolonial criticism to investigate the text’s anticolonialist ideology and approaches to resist the colonialist domination and deal with the postcolonial condition. The analysis reveals that the text presents an anticolonialist sentiments through marginal characters who are conditioned by the sense of unhomeliness as a result of their socioeconomic disadvantages. The text then subverts the colonialist ideology by secularising Christian terminologies and revisiting a literary canon from the point of view of the underclass. Finally, the text suggests that conflicting postcolonial identities can be reconciled and hybridised through respect and recognition at an individual level.